2017
DOI: 10.3390/tropicalmed2010004
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Risk Factors Associated with Malaria in the Highlands of Ethiopia: What Do We Need to Know?

Abstract: Malaria has been Ethiopia’s predominant communicable disease for decades. Following the catastrophic malaria outbreak in 2003–2004, the Federal Ministry of Health (FMoH) took drastic public health actions to lower the burden of malaria. The FMoH achieved significant declines in malaria mortality and incidence, and recently declared its objective to achieve malaria elimination in low malaria transmission areas of Ethiopia by 2020. However, while the overall malaria prevalence has decreased, unpredictable outbre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 70 publications
2
31
0
Order By: Relevance
“…This agrees with several other previous studies conducted in different parts of Ethiopia that also reported predominance of P. vivax followed by P. falciparum and mixed infection of the two, respectively [40,41]. The current result is also consistent with findings reported outside Ethiopia [36,42].…”
Section: Discussionsupporting
confidence: 94%
“…This agrees with several other previous studies conducted in different parts of Ethiopia that also reported predominance of P. vivax followed by P. falciparum and mixed infection of the two, respectively [40,41]. The current result is also consistent with findings reported outside Ethiopia [36,42].…”
Section: Discussionsupporting
confidence: 94%
“…Parasitological diagnosis among febrile patients provides data that assists malaria-endemic countries to determine their malaria status within the malaria elimination continuum [ 5 – 7 ]. Additionally, elucidating determinants of malaria parasitaemia is useful in informing the deployment of proven interventions to yield maximum impact [ 8 10 ]. We report the prevalence of malaria parasitaemia and mRDT diagnostic performances among febrile patients who participated in a nation-wide survey on HRP2 gene deletion conducted in selected health care facilities between May and August 2018.…”
Section: Introductionmentioning
confidence: 99%
“…The Plasmodium species causing malaria in Ethiopia are Plasmodium falciparum , accounting for about 60% of cases, and Plasmodium vivax , which accounts for about 40% of cases, with the former being the cause of most severe clinical manifestations and deaths [4, 6]. Current case management protocols target both species [4, 5], but may not be adequate for other Plasmodium species.…”
Section: Introductionmentioning
confidence: 99%